ESTUDO DE CASO DE UM CRIME ANUNCIADO NA CIDADE DE SALVADOR - Silva, Marinalva Ribeiro da (2010)
To present dissertation this intends to analyzes the application of the Law Maria da Penha, starting from the specific case of a woman's homicide, victim of domestic and family violence, to evidence the impediments in the efetivation of the law, in the protective system in her foreseen, considering the violence concept; the main public politics of protection to the woman, in the service policeman to the woman in violence situation, in terms of measures adopted by the Public prosecution service, Judiciary and for the civil police. The questions bitter husband with the separation, after several aggressions, finished, after two attempted murders, committing the crime in fact. In spite of the Law Maria da Penha to bring in this salience, in the art. 3rd, §1st the compulsory nature of adoption of public politics for the public power, what do seek to protect the women's human rights, but, in fact, what has been made by the responsible organs in giving effectiveness the law? How are the integrated services acting in the municipal district of Salvador? It was select for DEAM and it has been processed by this judgement. The victim had already denounced the aggressions previous to the authorities, but they was died, for the husband aggressor, on March 24, 2009; they was made the researcher's participant observation in two DEAMs. The adopted methodology consisted of the bibliographical and documental research, considering the documentation of the case collected close to 2nd Stick of the Jury, where the homicide crime, happened in the Salvador city. The conclusion the one that she arrived was that in the specific case of the analyzed homicide, and that it is processed in the 2nd Pierces Summaries of Salvador, misunderstandings were detected in the application of new law, on the part of Promoters of Justice that acted in the cases of violence that preceded the victim's death, to example of requesting information to MM Judgement's registry office to know of the existence or not of ACCUSATION crime against the accused, when it is the own organ that denounces; in informing that the criminal procedure was in phase of diligences in the Police station of origin Police, when actually the Inquiry Policeman n° 086/2007, was in the Public prosecution service, of having said for the procedure of the Law nº 9.099/90, literally prohibited for the Law Maria da Penha; of having informed the inexistence of REPRESENTATION for the aggressor's protective custody, etc.; and, in spite of the Law Maria da Penha to be efficient, this effectiveness, in the Justice of Bahia, it is still seen with some impediments in the application in the foreseen protective system. The statistics demonstrate that the aggressions lived in the domestic and family atmosphere are projected in the space extra moors, reaching, besides, all the collectivity, with the consequent banalization of the violence.